Plan de negocios de exportación de panela granulada para el mercado de España. - Escobar Manrique, Ana Janeth (My University, 2020)
In this research word within the framework of the complex modality titling process, the objective is to design a business plan for the export of granulated panela to Spanish market. The business plan is a tool for companies, allows to investigate the market and trace a route of export logistics, generate product marketing strategies obtaining competitiveness and acceptance in the market. It is noted that the signing of a commercial agreement between Ecuador and the European Union generates benefits in export since many products can enter with zero tariffs on the European market. In this sense ,there are market opportunities that motivate Ecuadorian companies to expand their businesses (Andrade & Meza , 2017). The depletion of resources, climate change and malnutrition are affecting society and the sector, as food security systems must be improved, which must be more sustainable with the environment, according to the context of the European Green Agreement. You must have responsible business conduct with consumers. Products that enter Spain must comply with the documentation, the specific sector norms, the necessary regulations so that the products can be exported to the EU, quality and standardized safety builds confidence in European consumers. In the market research that supports the export business plan, basic information on the destination market was obtained, the trend of consumption of Europeans with respect to food products was identified. The trend is oriented to the natural and organic healthy product.
En este trabajo de investigación en el marco del proceso de titulación modalidad complexivo, se plantea el objetivo de diseñar un plan de negocios para la exportación de panela granulada para el mercado de España. El plan de negocio es una herramienta para las empresas, permite investigar al mercado y trazar una ruta de la logística exportadora, generar estrategias de comercialización de producto obteniendo competitividad y aceptación en el mercado. Se destaca que la firma de un acuerdo comercial entre Ecuador y la Unión Europea genera beneficios en las exportaciones ya que muchos productos pueden ingresar con cero aranceles al mercado europeo. En este sentido, existen oportunidades de mercado que motivan a las empresas ecuatorianas a expandir sus negocios. (Andrade & Meza , 2017) El agotamiento de los recursos el cambio climático y la desnutrición están afectando a la sociedad y al sector, por cuanto se debe mejorar los sistemas de seguridad alimentaria los cuales deben ser más sostenibles con el medio ambiente, según el contexto del Acuerdo Verde Europeo, se debe tener una conducta comercial responsable con los consumidores. En la investigación de mercado que sustenta el plan de negocios de exportación se obtuvo información básica del mercado de destino, se identificó la tendencia de consumo de los europeos con respecto a productos alimenticios. La tendencia está orientada a lo natural y orgánico, que no hayan sido procesados o refinados, he aquí la oportunidad de negocio de exportar panela granulada por ser un producto orgánico y saludable.
Keywords: PLAN DE NEGOCIOS DE EXPORTACIÓN; PANELA GRANULADA; ESTRATEGIA DE COMERCIALIZACIÓN; ACUERDO COMERCIAL CON LA UNIÓN EUROPEA